Gender Differences in Children Mental Health Disorders after Earthquakes in Iran: A Systematic Review - Hamed Seddighi; Ibrahim Salmani (Shahid Sadoughi University of Medical Sciences, 2019)
Introduction: Earthquake occurs in the world every year and Iran is one of the most earthquake-prone countries in the world with the ranking of 15 between 120 countries. Children are the most vulnerable group in disasters and they have a number of negative symptoms after a disaster. Methods: This study used the systematic review method and followed systematic review principles. Mental health, earthquake, psychosocial, PTSD, post-traumatic stress disorder, and stress were the keywords used to search in the Iranian scientific information database (SID), Noor Specialized Magazines (Noormags) and Google Scholar. The language of the search was Farsi and just Farsi articles were included in the review. Results: The result were presented in five sections (Psychosocial interventions, Signs of disorder, Gender, Age, Geographical area). It showed psychosocial interventions of those studied in reviewed papers were effective and there were gender differences in children mental health disorders after earthquakes in Iran. In addition, PTSD group, girls reported all the symptoms of PTSD more than the boys except anger symptoms, , but the prevalence of PTSD symptoms in males was higher than in girls. Conclusion: Iranian studies just focused on male and female gender and found that disorders are higher in girls of different ages in childhood. In the age group of 13 to 18 years, the frequency of each disorder was less than that of the seven to twelve-year old group.